1988
DOI: 10.1530/jrf.0.0830819
|View full text |Cite
|
Sign up to set email alerts
|

The fertility of hypothyroid male mice

Abstract: Summary. Male mice homozygous for the hypothyroid gene mutation were compared with normal siblings to determine whether hypothyroidism induced infertility by impairing sexual behaviour. In addition, the fertility of the hypothyroid mice was examined. The experimental results provide unequivocal evidence that genetically\x=req-\ induced hypothyroidism in male mice does not impair sexual behaviour or cause infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Impaired viability in D3KO mice may be due to perinatal thyrotoxicosis, as a similar observation has been made in rats and humans (48,49). Concerning the reproductive function of the D3KO mouse, severe hypothyroidism may affect fertility in both sexes, as demonstrated by hyt/hyt mice (50,51). Of note, fertility in the TRH KO mouse, which manifests a milder degree of hypothyroidism that is similar to that in the D3KO mouse, is normal (32).…”
Section: Figurementioning
confidence: 53%
“…Impaired viability in D3KO mice may be due to perinatal thyrotoxicosis, as a similar observation has been made in rats and humans (48,49). Concerning the reproductive function of the D3KO mouse, severe hypothyroidism may affect fertility in both sexes, as demonstrated by hyt/hyt mice (50,51). Of note, fertility in the TRH KO mouse, which manifests a milder degree of hypothyroidism that is similar to that in the D3KO mouse, is normal (32).…”
Section: Figurementioning
confidence: 53%
“…Thyroidectomy in immature male rats caused severe inhibition of gametogenesis and Leydig cell development (Chowdury and Arora, 1984;. Hypothyroid male mice were infertile in 1 study (Beamer et al, 1981) but fertile in others (Chubb and Nolan, 1985;Chubb and Henry, 1988). Hypothyroidism had a depressive effect on libido in stallions (Lowe et al, 1975), but no such effect was observed in hypothyroid male rats (Cooke et al, 1991).…”
Section: Hormonal Treatments Aimed At Natural Pregnanciesmentioning
confidence: 99%
“…An example might be the relationship between hypothyroidism and infertility. It is possible that this link exists, and there may be sufficient evidence to conclude that there is a relationship between the two, but available data may not be sufficient to establish a statistical model of the relationship (Lincoln et al, 1999;Chubb & Henry, 1988). In many cases, the scientists simply do not know what effects will be seen in humans.…”
Section: Identification Of Health Effectsmentioning
confidence: 99%